Basic immunology : functions and disorders of the immune system - Abbas, Abul K.; Lichtman, Andrew H. ;Pillai, Shiv ;Baker, David L. ;Baker. Alexandra (Philadelphia, Pennsylvania : Elsevier, Saunders, 2014)
Understand all the essential concepts in immunology with Basic Immunology: Functions and Disorders of the Immune System! This concise, focused text provides you with an up-to-date, accessible introduction to the workings of the human immune system. This text provides you with an up-to-date, accessible introduction to the workings of the human immune system. Efficiently master the immunology information you need through clinically focused content, logically organized by mechanism. Apply what you've learned to real-world situations by referencing the appendix of clinical cases. Enhance your learning with the help of numerous full-color illustrations and useful tables, as well as summary boxes, review questions, and a glossary of immunology terms. Study immunology anywhere!
Introduction to the immune system -- Innate immunity -- Antigen capture and presentation to lymphocytes -- Antigen recognition in the adaptive immune system -- T cell-mediated immunity -- Effector mechanisms of t cell-mediated immunity -- Humoral immune responses -- Effector mechanisms of humoral immunity -- Immunological tolerance and autoimmunity -- Immune responses against tumors and transplants -- Hypersensitivity -- Congenital and acquired immunodeficiencies.
Includes bibliographical references and index.
Keywords: IMMUNOLOGY